2013
DOI: 10.3389/fnhum.2013.00440
|View full text |Cite
|
Sign up to set email alerts
|

Effortless awareness: using real time neurofeedback to investigate correlates of posterior cingulate cortex activity in meditators' self-report

Abstract: Neurophenomenological studies seek to utilize first-person self-report to elucidate cognitive processes related to physiological data. Grounded theory offers an approach to the qualitative analysis of self-report, whereby theoretical constructs are derived from empirical data. Here we used grounded theory methodology (GTM) to assess how the first-person experience of meditation relates to neural activity in a core region of the default mode network—the posterior cingulate cortex (PCC). We analyzed first-person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
140
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(162 citation statements)
references
References 25 publications
13
140
0
Order By: Relevance
“…Compared to the observing mode of direct experience of the meditators, controls might have entered a more cognitive elaborative mode, although this specific interpretation needs to be addressed in follow-up studies. This view supports the results of recent studies (Jo, Wittmann, Borghardt, et al, 2014;Garrison et al, 2013) that experienced meditators are suitable participants for the difficult task of relating introspective first person data with third person measurements.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to the observing mode of direct experience of the meditators, controls might have entered a more cognitive elaborative mode, although this specific interpretation needs to be addressed in follow-up studies. This view supports the results of recent studies (Jo, Wittmann, Borghardt, et al, 2014;Garrison et al, 2013) that experienced meditators are suitable participants for the difficult task of relating introspective first person data with third person measurements.…”
Section: Discussionsupporting
confidence: 90%
“…The deactivation of this important hub of the DMN has been related to effortless awareness (Garrison et al 2013a) and was also found deactivated in an fMRI study during focused attention meditation (Garrison et al 2013b). PCC deactivation reportedly reflects increased present-centered awareness, whereas PCC activation is related to being caught up in mental content and is associated with decreased attention (Brewer et al 2013).…”
Section: Discussionmentioning
confidence: 96%
“…A study utilizing the first-person narratives of the meditating participants suggested that the better the participants can stop thinking, the better they can inhibit the activity in the PCC; conversely, PCC activity was related to the spontaneous thoughts when these participants were effortfully contriving to self regulate [46].…”
Section: Some Considerations On the Brain Substrates Of The Agir Modelmentioning
confidence: 99%